Analysis of Risk Management Implementation in the Cleaning Process of Coffee Roasting Machines at Manufacturing Industry Using Risk Identification and Matrix Approach - Ramadhanti, Lifia Citra; Toyosito, Rakay Edhiargo; Hidayat, Rahmat (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
This study aims to identify and analyze occupational safety risks during the cleaning process of large-capacity coffee roasting machines at manufacturing industry. The method used is quantitative descriptive analysis with a risk assessment approach, using the SNI ISO 31000:2018 standard. Data were collected through interviews, direct observation, and literature studies. The results of the study indicate that the main risks include slipping, falling from a height, contact with sharp or hot objects, physical fatigue, and the risk of electrical contact. The risks with the highest severity are falling from a height and electrical contact, which are exacerbated by the lack of occupational safety facilities such as signs and personal protective equipment (PPE). Through a risk matrix and fishbone analysis, a mitigation strategy was designed in the form of installing safety facilities, implementing standard operational procedures, occupational health and safety (OHS) training, and routine inspections. The implementation of these steps is expected to create a safer work environment, increase efficiency, and support operational sustainability at manufacturing industry.